2016
DOI: 10.1016/j.energy.2016.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Method to investigate and plan the application of low temperature district heating to existing hydraulic radiator systems in existing buildings

Abstract: Document Version Peer reviewed version Link back to DTU Orbit Citation (APA):Tunzi, M., Østergaard, D. S., Svendsen, S., Boukhanouf, R., & Cooper, E. (2016). Method to investigate and plan the application of low temperature district heating to existing hydraulic radiator systems in existing buildings. Energy, 113,[413][414][415][416][417][418][419][420][421] This study presents a method to adapt existing hydronic systems in buildings to take advantage of low temperature district heating (LTDH). Plate radiators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Building renovation was not taken into account in this study. In addition, the average heat gains from occupants and equipment can be assumed as 0.81 and 1.55 W/m 2 respectively [34]. If those heat gains were added, the oversizing of radiators would increase 5~10 %, the final value of oversizing will range from 21 to 27%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Building renovation was not taken into account in this study. In addition, the average heat gains from occupants and equipment can be assumed as 0.81 and 1.55 W/m 2 respectively [34]. If those heat gains were added, the oversizing of radiators would increase 5~10 %, the final value of oversizing will range from 21 to 27%.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Some DH companies incentivize their customers through motivation tariffs to reduce their temperatures in exchange of discount in their energy bills. Researches show that low return temperature has higher economic benefits, and DH companies care more about low return temperature than low supply temperature [34].…”
Section: Scenariosmentioning
confidence: 99%
“…This circumstance is caused by the fact that the comfort temperature is not maintained inside that leads to overheating and excessive fuel consumption. Works [8][9][10][11][12] show the positive use of thermostatic valves on heating radiators. And the article [13] gives the analysis of the control quality of a thermostatic valve.…”
Section: Discussionmentioning
confidence: 99%
“…Sameti and Haghighat [19] demonstrated that additional energy savings in district heating systems can be achieved by expanding heat exchange among several buildings, which can lead to a 25 % reduction in annual costs. Whereas Tunzi et al [20] investigated the application of LTDH to hydraulic radiators by adjusting temperatures according to demand, and found that it can lead to a discount of 14 % to 16 % in annual energy bills.…”
Section: Introductionmentioning
confidence: 99%